A Chromo-fluorogenic synthetic "Canary" for CO detection based on a Pyrenylvinyl Ruthenium(II) complex - Moragues,ME; Toscani,A; Sancenon,F; Martinez-Manez,R; White,AJP; Wilton-Ely,JDET (Journal of the American Chemical Society, 2014)
The chromo-fluorogenic detection of carbon monoxide in air has been achieved using a simple, inexpensive system based on ruthenium(II). This probe shows exceptional sensitivity and selectivity in its sensing behavior in the solid state. A color response visible to the naked eye is observed at 5 ppb of CO, and a remarkably clear color change occurs from orange to yellow at the onset of toxic CO concentrations (100 ppm) in air. Even greater sensitivity (1 ppb) can be achieved through a substantial increase in turn-on emission fluorescence in the presence of carbon monoxide, both in air and in solution. No response is observed with other gases including water vapor. Immobilization of the probe on a cellulose strip allows the system to be applied in its current form in a simple optoelectronic device to give a numerical reading and/or alarm.